(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2025)
Physical and chemical characteristics of soil samples taken from the María Lucía Metropolitan Park, located in the Llanerita Trail of the municipality of Villavicencio, Meta Department, Colombia. In this sense, four calicatas were opened, identified with symbols composed of four capital letters and a consecutive number, up to three figures. Thus, the type of sampling was non-probabilistic, intentional or opinionated, which is a selection procedure in which the probability that population elements have to integrate the sample is unknown; and the elements are chosen on the basis of criteria or judgements set by the investigator, in these samples were determined: texture, wet colour, presence of spots, thick fragments, consistency, structure, root presence, biological activity, surface features, resistance to penetration, moisture, pH. The soils identified and described were found in the livestock area of the park, where they presented textural classes ranging from sandy clay, silty clay and loamy clay, with dark color nuances, in addition, little presence of mottled, thick fragments and roots, low resistance to penetration and moisture. These were categorized as not very compact, with little presence of sand or silt cutaneous and low biological activity especially in subsurface horizons. The pH of these soils was extremely to slightly acidic. According to these physical and chemical characteristics, these soils could still be used for livestock farming; however, it is suggested that other soil characteristics such as real density, apparent density, organic matter, soil phosphates, to identify other uses.